Persepsi Petani terhadap Aspek Teknis Komoditi Kelapa Sawit di Desa Ladang Peris Kecamatan Bajubang Kabupaten Batanghari - Shinta Anggreany; Arsyad Lubis; Idris Sardi (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2013)
The cultivation of oil palm in the Province of Jambi is growing rapidly, this condition influenced by the farmer's decision to select the commodity in farming. The decision influenced by the thair perceived, knowledge and experience. The technical aspects include time needed incultivation practice and harvesting, and knowledge of pests and diseases. This research aimed to analyze the perception of the palm in technical aspects. This research was conducted in Ladang Peris village, District Bajubang, Batanghari District with 29 respondents from May 26, 2011 until June 26, 2011. Data analysis is based on qualitative methods. The results showed that the perception of farmers on the tecnical aspects of oil palm focused on easy cultivation practice, harvesting once in two weeks period, and less pests and diseases infestation as compared to rubber plant.Keywords: Perception of farmers, technical aspects, palm